Construct of Carbon Nanotube-Supported Fe2O3 Hybrid Nanozyme by Atomic Layer Deposition for Highly Efficient Dopamine Sensing - Yang, Yingchun; Li, Tao; Qin, Yong; Zhang, Lianbing; Chen, Yao (Frontiers in Chemistry, 2020)
The Fe2O3 nanozyme has been identified as the most promising alternative for the Fe3O4 nanozyme due to its relatively low toxic risk and good chemical stability. However, its enzyme-like activity is relatively low enough to meet specific application requirements. Furthermore, previous synthesis approaches have difficulties in fabricating ultra-small Fe2O3 nanoparticles with tunable size and suffer from agglomeration problems. In this study, atomic layer deposition (ALD) was used to deposit Fe2O3 on surfaces of carbon nanotubes to form hybrid nanozymes (Fe2O3/CNTs). ALD enables the preparation of ultrafine Fe2O3 nanoparticles with precise size control <1 nm, while CNTs could be served as promising support for good dispersibility and as an effective activity activator. Hence, the formed Fe2O3/CNTs exhibit excellent peroxidase-like activity with a specific peroxidase activity of 24.5 U mg−1. A colorimetric method for sensing dopamine (DA) was established and presented good sensitivity with a limit of detection (LOD) as low as 0.11 μM. These results demonstrated that, in virtue of meticulous engineering methods like ALD, carbon nanomaterial-based hybrids can be developed as talented enzyme mimetic, thus paving a way for nanozyme design with desired activity and broadening their applications in biosensing and other fields.